2014
DOI: 10.1159/000362626
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Soluble Vascular Adhesion Protein-1 Level and Gastric Cancer Prognosis

Abstract: Background: Vascular adhesion protein-1 (VAP-1) is a glycoprotein that mediates tissue-selective lymphocyte adhesion in a sialic acid-dependent manner. The prognostic importance of VAP-1 was determined in various human cancers. The aim of this study was to determine the relationship between VAP-1 and prognosis of gastric cancer. Materials and Methods: Serum of operable and metastatic gastric cancer patients was collected before treatment (surgery, radiotherapy, and/or chemotherapy). VAP-1 levels were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…For example, VAP-1 SSAO activity is now considered a potential target for anti-inflammatory therapy (13). Other studies have shown that serum VAP-1 is higher than normal in hepatocellular cancer (14) and has an inverse correlation with disease stage in gastric cancer (15). Our recent study also found VAP-1 could be a promising prognostic biomarker in astrocytoma (16).…”
supporting
confidence: 54%
“…For example, VAP-1 SSAO activity is now considered a potential target for anti-inflammatory therapy (13). Other studies have shown that serum VAP-1 is higher than normal in hepatocellular cancer (14) and has an inverse correlation with disease stage in gastric cancer (15). Our recent study also found VAP-1 could be a promising prognostic biomarker in astrocytoma (16).…”
supporting
confidence: 54%
“…VAP-1 is one of the endothelial adhesion molecules which supports shear-dependent lymphocyte binding to high-endothelial venules in lymph nodes [ 14 , 28 ]. A number of studies have suggested a strong correlation between serum VAP-1 levels and cancer prognosis [ 18 , 19 , 21 ]. One recent study showed that the serum VAP-1 level was significantly lower in the colorectal cancer group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum VAP-1 levels in chronic liver disease and multiple sclerosis compared to healthy individuals have been reported previously [ 16 , 17 ]. In addition, low serum VAP-1 is associated with disease relapse and worse prognosis in colon cancer and gastric cancer [ 18 21 ]. However, the diagnostic and prognostic values of serum VAP-1 for TC, particularly before surgery, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are either general tumor markers or proteins that are associated with signaling related to carcinogenesis such as cell proliferation, angiogenesis or inflammation. These proteins include CEA (Carcinoembryonic Antigen) ( [14], CA125 (Cancer Antigen 125) [14], CA19-9 (Cancer Antigen 19-9) [14,15], AFP (Alpha-Fetoprotein) [16,17], Pyruvate M2 Kinase [15,18], serum amyloid A [19,20], macrophage migration inhibitory factor [21,22], Leptin [23], dickkopf [24,25], olfactomedin 4 [26], VAP-1 [27,28], UPA [29,30], Cathepsin B [30][31][32], HMW kininogen [33], P53 antibody [34,35], cytokeratin 18 [36][37][38], RegIV [39], IPO-38 [40], S100A6 [41], thrombin light chain [42], fibrinopeptide A [43,44], angiopoietin-like protein 2 [45][46][47]. CEA, CA125, CA19-9, AFP, M2 Pyruvate Kinase are common tumor markers also overexpressing in other type of cancers [48][49][50][51][52]…”
Section: Serum Protein Biomarkers Of Gastric Cancermentioning
confidence: 99%